In a 19th century psychologist’s laboratory - Domarańczyk-Cieślak, Daria (In the Mirror of Things, 2022)
This article deals with the topic of the first psychological laboratories in the world. Their history began in 1879 when Wilhelm Wundt established his experimental laboratory in Leipzig, where numerous experiments in psychophysiology were carried out under his direction, those examining the cognitive processes and the nature of human emotions being of particular importance. That is why the year 1879 is recognised as the symbolic date of birth of psychology as a separate and independent science. Soon afterwards, more and more psychological laboratories were established across Europe and the USA which significantly spurred the development of this newly born science. Some experimental laboratories were also set up on the Polish territories under partitions – in Cracow, Lvov and Warsaw. At the initiative of Julian Ochorowicz, called ‘the father of Polish psychology’, a private laboratory was established in the town of Wisla, where hypnotic and spiritualistic séances together with scientific experiments were carried out. And, therefore, the town itself has become the informal capital of Polish psychology.